Consumer acceptance of foods derived from blended wheat flour in Nairobi, Kenya - Kariuki, Sarah Wairimu; Donovan, Jason; Muteti, Francisca N.; Ibba, Maria Itria; Muoria, John; Mahugu, Alex; Sila, Daniel; Bentley, Alison (Elsevier, 2025)
Governments across Africa have shown enthusiasm for wheat flour blending to reduce food security risks and pull demand for traditional but underutilized crops. However, research has sidestepped the question of whether consumers will accept foods derived from blended wheat flour. We used sensory evaluation and contingent valuation techniques with a sample of 1871 consumers in Nairobi, Kenya to measure the acceptance of two commonly consumed foods (chapati and bread) made from wheat flours blended with up to 20% sorghum, millet, or cassava flour. In blind tasting, bread made of blended flour was slightly less preferred than conventional bread, while chapati products made of wheat and sorghum (10%) or millet (5%) blends were equally valued as chapati made of 100% wheat flour, suggesting the potential to replace up to 10% of wheat flour in chapati without compromising sensory characteristics and consumer acceptance. When informed about the flour composition before tasting, consumers showed a stronger preference for the products made from blended flour and expressed a higher willingness to pay for blend-based products than conventional products. We discuss the policy implications of how consumer interest in such foods can be harnessed to advance food security and economic development goals.